Mitome: dynamic and interactive database for comparative mitochondrial genomics in metazoan animals - Lee, Yong Seok (Oxford University Press, 2008)
Mitome is a specialized mitochondrial genome database designed for easy comparative analysis of various features of metazoan mitochondrial genomes such as base frequency, A+T skew, codon usage and gene arrangement pattern. A particular function of the database is the automatic reconstruction of phylogenetic relationships among metazoans selected by a user from a taxonomic tree menu based on nucleotide sequences, amino acid sequences or gene arrangement patterns. Mitome also enables us (i) to easily find the taxonomic positions of organisms of which complete mitochondrial genome sequences are publicly available; (ii) to acquire various metazoan mitochondrial genome characteristics through a graphical genome browser; (iii) to search for homology patterns in mitochondrial gene arrangements; (iv) to download nucleotide or amino acid sequences not only of an entire mitochondrial genome but also of each component; and (v) to find interesting references easily through links with PubMed. In order to provide users with a dynamic, responsive, interactive and faster web database, Mitome is constructed using two recently highlighted techniques, Ajax (Asynchronous JavaScript and XML) and Web Services. Mitome has the potential to become very useful in the fields of molecular phylogenetics and evolution and comparative organelle genomics. The database is available at: http://www.mitome.info.